Sociocultural identity lens in language research: Issues, insights, and future directions - Dr. Imdad Ullah Khan (JSSH, 2024)
Learners’ identities are socially situated and historically contingent. For bi- /multilingual students of English as a Foreign Language (EFL), it is important classroom activities and pedagogic approaches support their existing sociocultural and linguistic resources and promote empowering identities among learners. This review article provides a critical analysis of a growing body of research literature that deals with learners’ identities from a sociocultural perspective. It synthesizes major themes in this area of research and analyzes significant insights it offers for effective English as a Foreign Language (EFL) teaching, protection of local language, and indigenous cultural norms. The article first provides a review of the development of a sociocultural focus in language learning and identity research.